ESTIMATION OF THE SHAPE PARAMETER IN LOMAX DISTRIBUTION BASED ON INTERVAL DATA - LONG Bing; XI ChangXin (Jixie qiangdu)
The maximum likelihood method is used to estimate the unknown shape parameter in Lomax distribution under interval data, the expression of the shape parameter can not be obtained.The iterative formula of shape parameter can be obtained by using EM algorithm, it is easy to get the estimated value and the estimation has good convergence. Random simulation results show that EM algorithm has high accuracy, and the final estimation is independent of initial value.